2020
DOI: 10.15184/aqy.2019.230
|View full text |Cite
|
Sign up to set email alerts
|

The VIMOA project and archaeological heritage in the Nuussuaq Peninsula of north-west Greenland

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…The results showed that by 2100, 45%-61% of all cultural features may be lost on the background of increasing coastal erosion and sedimentation processes. Darwent et al (2019) and Walsh, Ballinger, et al (2020); Walsh, Tejsner, et al (2020) demonstrated, through basic research such as repeated photography, that the Arctic coastlines at the site of Iita and five sites from Nuussuaq Peninsula (Northwestern Greenland) were eroding. Studies from Svalbard over the period 1927-2020 showed an erosion rate of -0.14 m/yr.…”
Section: Sea Ice Decline Related Hazards (Coastal Erosion)mentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that by 2100, 45%-61% of all cultural features may be lost on the background of increasing coastal erosion and sedimentation processes. Darwent et al (2019) and Walsh, Ballinger, et al (2020); Walsh, Tejsner, et al (2020) demonstrated, through basic research such as repeated photography, that the Arctic coastlines at the site of Iita and five sites from Nuussuaq Peninsula (Northwestern Greenland) were eroding. Studies from Svalbard over the period 1927-2020 showed an erosion rate of -0.14 m/yr.…”
Section: Sea Ice Decline Related Hazards (Coastal Erosion)mentioning
confidence: 99%
“…Coastal erosion rates in the Arctic are among the highest on earth (Walsh, Ballinger, et al, 2020; Walsh, Tejsner, et al, 2020). The average rate was calculated at –0.5 m/yr for the entire Arctic coast.…”
Section: Impacts Of Climate Change On Immovable Cultural Heritage In ...mentioning
confidence: 99%
“…Case studies from elsewhere in the circumpolar Arctic have demonstrated how UAVs have assisted heritage researchers in harsh environments with a remote sensing platform that is affordable, versatile, and customizable due to swappable sensor payloads [24][25][26][27][28]. Ecological research in other cold climates has also benefited from the use of UAV technology [29].…”
Section: Remote Sensing Strategies In the Y-k Delta: Satellites Vs Dr...mentioning
confidence: 99%
“…Therefore, the western end of the Vaigat Strait was selected for the Vaigat Iceberg-Microbial Oil degradation and Archaeological heritage investigation (VIMOA), which was carried out from 29 July to 16 August, 2019. The multidisciplinary research objectives included investigations of iceberg drift and deterioration, oil degradation by microbes, coastal archaeological sites [38], and testing new technology for iceberg monitoring [39,40].…”
Section: Vaigat Straitmentioning
confidence: 99%